2021
DOI: 10.1186/s12913-021-06191-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrete choice experiment for eliciting preference for health services for patients with ALS and their informal caregivers

Abstract: Background Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative condition with a mean life expectancy of 3 years from first symptom. Understanding the factors that are important to both patients and their caregivers has the potential to enhance service delivery and engagement, and improve efficiency. The Discrete Choice Experiment (DCE) is a stated preferences method which asks service users to make trade-offs for various attributes of health services. This method is used to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 29 publications
(3 reference statements)
2
29
0
Order By: Relevance
“…Studies were conducted in Australia,46 47 52 the USA,24 25 32 33 41 55 56 58 Canada,27 28 35 53 59 Denmark,50 UK,23 43 48 54 Ireland,37 South Korea,21 29 30 34 39 40 57 Taiwan,36 38 Singapore,31 Germany,22 26 51 Hong Kong42 and the Netherlands 44 45 49. Quantitative studies reported more on factors associated with concordance and/or discordance while qualitative studies reported on reasons for and/or processes underpinning concordance and discordance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were conducted in Australia,46 47 52 the USA,24 25 32 33 41 55 56 58 Canada,27 28 35 53 59 Denmark,50 UK,23 43 48 54 Ireland,37 South Korea,21 29 30 34 39 40 57 Taiwan,36 38 Singapore,31 Germany,22 26 51 Hong Kong42 and the Netherlands 44 45 49. Quantitative studies reported more on factors associated with concordance and/or discordance while qualitative studies reported on reasons for and/or processes underpinning concordance and discordance.…”
Section: Resultsmentioning
confidence: 99%
“…The studies investigated a range of palliative and end-of-life care domains and contexts, including place of death,23 24 35 36 46 48 54 advance care planning and advance directives,30 39 42 52 53 57 euthanasia,45 artificial nutrition and hydration,22 43 cardiopulmonary resuscitation,27 29 hospice care,21 49 end-of-life care in general (including life-sustaining treatment, life-extending treatment and treatment approaching death)23 25 38 47 and, more broadly, care over the disease trajectory 50 51. Other studies focused more specifically on patients and family caregivers’ preferences, values and judgements with respect to care,28 32–34 37 40 55 and on the family caregiver and the broader family role in the decision-making process 26 31 41 44 56 58 59. Although many studies examined concordance in care preferences and decision-making between patients and family caregivers, only nine studies explicitly focused on discordance, disagreement and/or conflict between patients and family caregivers 26 28 29 31 37 40 41 44 56…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations